2021
DOI: 10.3389/fmicb.2021.752750
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Importance of Abiotic and Biotic Factors Governing the Succession of Gut Microbiota Over Shrimp Ontogeny

Abstract: Intensive studies have evaluated abiotic factors in shaping host gut microbiota. In contrast, little is known on how and to what extent abiotic (geochemical variables) and biotic (i.e., surrounding microbes, younger shrimp, and age) factors assemble the gut microbiota over shrimp ontogeny. Considering the functional importance of gut microbiota in improving host fitness, this knowledge is fundamental to sustain a desirable gut microbiota for a healthy aquaculture. Here, we characterized the successional rules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…The gut microbial communities of shrimp are highly temporal dynamics over shrimp ontogeny, which are differed significantly even between an interval of a few days (Xiong et al ., 2017a; Zhang et al ., 2021). Similar pattern has also been observed in fishes (Yan et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbial communities of shrimp are highly temporal dynamics over shrimp ontogeny, which are differed significantly even between an interval of a few days (Xiong et al ., 2017a; Zhang et al ., 2021). Similar pattern has also been observed in fishes (Yan et al ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Similar pattern has also been observed in fishes (Yan et al ., 2012). Indeed, shrimp age is the most powerful predictor for the gut bacterial community, resulting in predictable assembly of the gut microbiota as shrimp aged (Xiong et al ., 2020; Zhang et al ., 2021). Thus, a key challenge is how to untangle the deviations of the gut microbiota between health status from these over host lifetime (Greenhalgh et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, this made the structure of the intestinal flora similar to that of the water but different from that of the sediment. It has also been suggested that the feed composition (He et al, 2017), environmental factors (Zhang et al, 2021), individual genetic development (Garibay-Valdez et al, 2020), and disease and season (Li et al, 2019) all influence the diversity of intestinal flora in L. vannamei. The specific factors influencing this warrant further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…P. vannamei farming has increased rapidly to meet the growing edible high-quality protein demand. Despite this, P. vannamei farming is constantly hampered by abiotic and biotic factors [ 58 ]. One of the challenges faced by P. vannamei farming relates to emerging diseases caused by bacteria, viruses, and fungi affecting the sustainability of shrimp [ 1 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%